Improved Learning Outcomes of Social Science Lessons Through Montase Technique - Wahyuni, Sri (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research was to improve student learning outcomes in social science grade  IV elementary shcool using montase technique. The reserach conducted was Classroom Action Research (PTK) with three cycles. The stages of each cycle are planning, implementing, observing, and reflecting. In teh first cycle the student who complete were 59,1%, the second were 63,64%, and the third were 81,82%. These result indicate that montase technique can improve student learning outcomes, especially in social science lessons in grade IV Nidaul Hikmah Islamic Integrated Elementary School.